Effect of weight change after renal transplantation on outcomes of graft survival - Sergio Barroso Hernández; Álvaro Álvarez López; Jorge Alberto Rodríguez Sabillón; Cristina López Arnaldo; Román Hernández Gallego; Elena García de Vinuesa Calvo; Juan Villa Rincón; Rosa María Díaz Campillejo; Nicolás Roberto Robles Pérez-Monteoliva (Nefrología (English Edition), 2022)
Background and objective: After kidney transplantation, there is an overall increase in weight, which may increase the risk of chronic kidney disease (CKD) and graft loss. But, not all patients gain weight, and the impact on the graft of this different evolution has not been well studied. The objective was to determine the causes of this different evolution and its effect on the graft. Patients and methods: Retrospective single-center cohort study of 201 patients followed up after transplantation, analyzing the determinants of the variation in weight at one year using logistic regression, and its effect on graft survival at the end of follow-up using Cox regression. Results: Globally, there was an average weight gain of 4.5 kg in the first year, but 26.6% lost weight. 37.2% increased their BMI, while 9.5% decreased it. The determinants of the different evolution of weight were age (OR for every 10 years: 0.6, p = 0.002), previous dialysis modality (ref. hemodialysis) (OR 0.3, p = 0.003), and BMI before transplantation (OR 0.9, p = 0.017). The different evolution of weight did not influence the final situation of the graft. The BMI at one year did influence as a continuous variable (HR 1.3, p = 0.003), and obesity, with a worse evolution (HR 7.0, p = 0.025). Conclusions: Although not all patients gain weight after kidney transplantation, the different evolution of weight does not influence graft survival. Resumen: Antecedentes y objetivo: Tras el trasplante renal se produce de manera global un incremento del peso pudiendo aumentar el riesgo de enfermedad renal crónica (ERC) y de pérdida del injerto. Pero no todos los pacientes ganan peso, y la repercusión sobre el injerto de esta diferente evolución, no está bien estudiado. El objetivo fue determinar las causas de esta diferente evolución y su efecto sobre el injerto. Pacientes y métodos: Estudio de cohortes retrospectivo unicéntrico de 201 pacientes seguidos tras el trasplante, analizando los determinantes de la variación del peso al año mediante regresión logística, y su efecto sobre la pérdida del injerto al final del seguimiento mediante regresión de Cox. Resultados: Globalmente se produjo durante el primer año un aumento de peso de 4,5 kg de media, pero un 26,6% perdieron peso. El 37,2% aumentó su índice de masa corporal (IMC), mientras que el 9,5% lo disminuyó. Los determinantes de la diferente evolución del peso fueron la edad (OR por cada 10 años: 0,6; p = 0,002), la modalidad de diálisis previa (ref. hemodiálisis) (OR: 0,3; p = 0,003) y el IMC previo al trasplante (OR: 0,9; p = 0,003). La diferente evolución del peso no influyó en la pérdida del injerto. Sí influyeron el IMC al año como variable continua (HR: 1,3; p = 0,003) y la obesidad, con peor evolución (HR: 7,0; p = 0,025). Conclusiones: Aunque no todos los pacientes ganan peso tras el trasplante renal, la diferente evolución del peso no influye en la supervivencia del injerto.